2015
DOI: 10.7324/japs.2015.501219
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro antioxidative potential of methanolic aerial extracts from three ethnomedicinal plants of Assam: A Comparative Study

Abstract: Antioxidants are the substances that neutralize free radicals or their actions. The traditional antioxidant phytochemicals from plants have been reported to inhibit the propagation of free radical reactions and to protect the human body from disease. The use of synthetic antioxidants has always been questioned because of their toxicity therefore researches are being carried out on plants nowadays to bring out the potent natural antioxidants. With this intent three ethnomedicinal plants of Assam viz., Calamus l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…DPPH• radical scavenging abilities were increased with the increased concentration of the test samples. The MEE exhibited 81% scavenging activity at the concentration of 1 mg/mL and our result is consistent with that of Mahato et al, [27],who investigated the methanol extract of L. spinosa for free radical scavenging activities and found moderate antioxidant activity. Phenolic compounds are reported as strong antioxidant compounds in different studies [28].…”
Section: Antioxidant Activitysupporting
confidence: 92%
“…DPPH• radical scavenging abilities were increased with the increased concentration of the test samples. The MEE exhibited 81% scavenging activity at the concentration of 1 mg/mL and our result is consistent with that of Mahato et al, [27],who investigated the methanol extract of L. spinosa for free radical scavenging activities and found moderate antioxidant activity. Phenolic compounds are reported as strong antioxidant compounds in different studies [28].…”
Section: Antioxidant Activitysupporting
confidence: 92%
“…Our results of ethanolic extract were accordance to the research conducted by Mohanty and, Sahoo G. in which they reported that Cedrus deodara Pinus roxburgii and Pinus wallachiana showed highest zone of inhibition against S. aureus, P. aeruginosa and E. coli [41].…”
Section: Discussionsupporting
confidence: 91%
“…Nowadays antioxidant phytochemicals, notably flavonoids and other polyphenol compounds from plants have been reported to inhibit the propagation of oxidant compounds like free radical and to protect the living system from disease caused by the oxidation process [8][9][10][11][12]. As a result extraction, characterization and the use of natural antioxidants from plants have been known to be a great progress [10][11][12].…”
Section: Introductionmentioning
confidence: 99%